2022
DOI: 10.5812/jcrps-128869
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes of In-hospital Cardiopulmonary Resuscitation: A Cross-Sectional Study in Iran

Abstract: Background: Taking into account the lack of information in this field in Iran, the present study aimed at assessing the five-year epidemiology and outcomes of in-hospital cardiopulmonary resuscitation (CPR) in educational centers in Kermanshah. Methods: A cross-sectional study was conducted on 1000 cases of resuscitation. The subjects were selected through systematic random sampling. Data gathering tool included a standard form of in-hospital resuscitation cases based on Utstein style and the framework of and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
0
1
Order By: Relevance
“…The largest number of resuscitated patients in this study (75.2%) were male. Contrary to a study done in Iran [ 19 ], the results showed no significant relationship between the outcome of CPR and gender. In addition, our study showed that a delay in epinephrine administration does not affect the outcome of CPR.…”
Section: Discussioncontrasting
confidence: 99%
“…The largest number of resuscitated patients in this study (75.2%) were male. Contrary to a study done in Iran [ 19 ], the results showed no significant relationship between the outcome of CPR and gender. In addition, our study showed that a delay in epinephrine administration does not affect the outcome of CPR.…”
Section: Discussioncontrasting
confidence: 99%